2016
DOI: 10.3390/molecules21040461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phlomis umbrosa Root on Longitudinal Bone Growth Rate in Adolescent Female Rats

Abstract: Abstract:This study aimed to investigate the effects of Phlomis umbrosa root on bone growth and growth mediators in rats. Female adolescent rats were administered P. umbrosa extract, recombinant human growth hormone or vehicle for 10 days. Tetracycline was injected intraperitoneally to produce a glowing fluorescence band on the newly formed bone on day 8, and 5-bromo-2 1 -deoxyuridine was injected to label proliferating chondrocytes on days 8-10. To assess possible endocrine or autocrine/paracrine mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…Actually, several studies have suggested that the level of IGFBP-3 may be superior to the measurement of IGF-1 in the diagnosis of GH deficiency, and in reflecting actual serum levels of IGF-1 [ 40 , 41 , 42 ]. In 2016, Lee et al also demonstrated that oral administration of Phlomis umbrosa root increased longitudinal bone growth rate by stimulating proliferation and hypertrophy of chondrocyte with the increment of circulating IGFBP-3 [ 43 ]. Furthermore, Kim et al reported that oral administration of herbal extracts increased the expression of IGF-1 and IGFBP-3 on the growth plate, and most rats had a direct proportional relationship between IGF-1 and IGFBP-3 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, several studies have suggested that the level of IGFBP-3 may be superior to the measurement of IGF-1 in the diagnosis of GH deficiency, and in reflecting actual serum levels of IGF-1 [ 40 , 41 , 42 ]. In 2016, Lee et al also demonstrated that oral administration of Phlomis umbrosa root increased longitudinal bone growth rate by stimulating proliferation and hypertrophy of chondrocyte with the increment of circulating IGFBP-3 [ 43 ]. Furthermore, Kim et al reported that oral administration of herbal extracts increased the expression of IGF-1 and IGFBP-3 on the growth plate, and most rats had a direct proportional relationship between IGF-1 and IGFBP-3 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall growth plate height and zonal height were measured by using ImageJ software (NIH, USA) at 3 locations as previously described [15]. …”
Section: Methodsmentioning
confidence: 99%
“…A total of 72 intact 21-day-old female Sprague–Dawley rats were purchased from Samtako Co. (Gyeonggi, Republic of Korea). The sample size was based on recent experiments conducted in our laboratory [ 11 ]. The rats were divided into four body weight groups (30–40, 40–50, 50–60, and 60–70 g).…”
Section: Methodsmentioning
confidence: 99%